Delignification Trends in Pretreatment of Musa Paradisiaca Pseudo-Stem and the Production of Bioethanol - Owofadeju, F. K.; Kolajo, T. E.; Onibudo, O. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This study was conducted to assess the potential of pre-treated Musa paradisiaca pseudo-stem as an alternative source of raw material for ethanol production. The pseudo-stem was pre-treated with NaOH and NaOH-AQ at varying time and liquor concentrations using a digester. Cellulose yield (CY) was determined gravimetrically, Residual Klason Lignin (RKL) was evaluated in accordance with TAPPI T236 standards and the effect of the pre-treatment variables were examined. Acid hydrolysis using dilute solutions of HCL and H2SO4 followed pre-treatment, while fermentation was achieved by the addition of an active yeast strain (Saccharomyces cerevisae). The ethanol produced was distilled, qualitative analysis was conducted using the Fourier Transform Infrared Spectroscopy (FTIR) and other standard methods. There was a general decrease in CY and RKL with increasing pulping time and alkali charge, using both NaOH and NaOH-AQ. CY ranged from 2.4 – 4.2g and 3.2 - 5.0g while RKL ranged from 2.46%-3.9% and 1.94-3.00% for both NaOH and NaOH-AQ pre-treatments respectively. However, there was significant difference between the effects of liquor concentration and time on CY at p=0.05. The addition of 0.1% anthraquinone to soda pulping liquor significantly increased CY and decreased RKL. The difference in glucose yields between the two dilute acid hydrolyses was not significant. Various qualitative tests on bio-ethanol showed traits very similar to the laboratory grade ethanol while FTIR confirmed the presence of ethanol. It is therefore proven that NaOH and NaOH-AQ are suitable pretreatment methods in the production of bioethanol from Musa paradisiaca.